2023
DOI: 10.3389/fpubh.2023.1295464
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination rates among healthcare workers: a systematic review and meta-analysis investigating influencing factors

Jingchun Fan,
Shijie Xu,
Yijun Liu
et al.

Abstract: IntroductionHealthcare workers risk of exposure to the influenza virus in their work, is a high-risk group for flu infections. Thus WHO recommends prioritizing flu vaccination for them–an approach adopted by >40 countries and/or regions worldwide.MethodsCross-sectional studies on influenza vaccination rates among healthcare workers were collected from PubMed, EMBASE, CNKI, and CBM databases from inception to February 26, 2023. Influenza vaccination rates and relevant data for multiple logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…A meta-analysis conducted by Fan et al from 92 studies comprised of 125 vaccination data points from 26 countries concluded that the overall influenza vaccination rates among health care workers was 41.7%. 3 The study identified factors that influenced vaccine uptake as age, length of employment, education level, area of work, occupation, coexisting medical conditions, perception of being at risk of infection, participation in vaccine training, and health education and knowledge of vaccine timing. 3 Although some members of the public were accepting of the new COVID-19 boosters, healthcare workers also encountered barriers similar to the public, which included mistrust in vaccines, misinformation related to vaccine safety and concerns of safe vaccine use during pregnancy.…”
Section: Background and Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis conducted by Fan et al from 92 studies comprised of 125 vaccination data points from 26 countries concluded that the overall influenza vaccination rates among health care workers was 41.7%. 3 The study identified factors that influenced vaccine uptake as age, length of employment, education level, area of work, occupation, coexisting medical conditions, perception of being at risk of infection, participation in vaccine training, and health education and knowledge of vaccine timing. 3 Although some members of the public were accepting of the new COVID-19 boosters, healthcare workers also encountered barriers similar to the public, which included mistrust in vaccines, misinformation related to vaccine safety and concerns of safe vaccine use during pregnancy.…”
Section: Background and Literature Searchmentioning
confidence: 99%
“… 3 The study identified factors that influenced vaccine uptake as age, length of employment, education level, area of work, occupation, coexisting medical conditions, perception of being at risk of infection, participation in vaccine training, and health education and knowledge of vaccine timing. 3 Although some members of the public were accepting of the new COVID-19 boosters, healthcare workers also encountered barriers similar to the public, which included mistrust in vaccines, misinformation related to vaccine safety and concerns of safe vaccine use during pregnancy. 5 The CDC’s MMWR weekly report 1 describes that healthcare workers whose employers’ neither required or recommended the vaccines had the lowest vaccine coverage, although the coverage with COVID-19 primary series vaccination was greater than 80% in all work settings possibly because of the prioritization of vaccination among health care workers and the vaccine mandates that existed during the pandemic.…”
Section: Background and Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation